A short review on novel biocomposites based on plant oil precursors - Mosiewicki, Mirna Alejandra (2013)
The last two decades have witnessed an exponential growth in the interest for using bioderived products in the polymer field, which is driven by the need to replace petroleum based materials and reduce the fuel consumption and, equally important, to produce materials that are more benign to the environment. Among the many products available from biomass, vegetable oils constitute a rich source for many different polymers and polymer precursors. In this review, the role of oil-based polymers as matrices for a wide variety of composites is presented, showing the importance of the selection of the filler/reinforcement to tailor the composite properties, in order to prepare structural or functional materials. Thus, a wide range of macro, micro and nanosized particles and fibers have been proposed, as well as organic and inorganic ones, in order to give answers to specific requirements. Although, the role of oil-based products may seem modest in some cases (partial replacement of synthetic materials), there is a clear trend to increase the percentage of "green"-based raw materials in the formulations of commodities as well as specialty polymers/composites for high added value applications.